The desire for longevity: Development of the Personal Longevity Scale. Issue 10 (2nd October 2016) - Adams-Price, Carolyn E.; Rush Smith, G.; Giesen, J. Martin; Morse, Linda W.
ABSTRACT: A new psychometrically acceptable measure of the desire to live a very long life was devised using two samples. In Study 1, initial exploratory analyses of the Personal Longevity Scale (PLS) scale revealed a two-factor structure. The Hope factor represents the hopefulness participants have with regards to their expectations about personal longevity. The second factor, Dread, represents the fear and uneasiness associated with self-perceptions of living a very long life. In Study 2, the bidimensional nature of the PLS measure was confirmed, and the scale was further refined to include a final of seven items. Four items represent Hope (α = .85), and three items represent Dread (α = .78). Theoretical rationales for the two-factor structure of personal longevity are discussed. In Study 3, the PLS was compared to three similar measures of attitudes about aging. The results indicate that the PLS has moderate levels of convergent and discriminant validity. Potential uses for the new scale are discussed.